Changes in Neutrophil to Lymphocyte Ratio, Lymphocyte to Monocyte Ratio, and Platelet to Lymphocyte Ratio During Palliative Radiotherapy May Predict Efficacy of Immune Checkpoint Inhibitor as Re-Challenge Treatment in Advanced Gastric Cancer: A Case Report - Chen, Jianxin; Wu, Xilin; Zhu, Shijian; Wang, Junhui (Frontiers in Oncology, 2022)
Introduction Immunotherapy with programmed death-1 (PD-1) inhibitors has emerged as frontline option in patients with advanced or metastatic gastric cancer. However, two-thirds of patients who received PD-1 inhibitors treatment still had disease progression in 1 year. Subsequent treatment strategies as salvage options always lead to limited efficacy. Case Description Herein, we presented a case of recurrent metastatic gastric adenocarcinoma that had progressed on first-line treatment with nivolumab, in which systematic inflammation parameters with neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), and platelet to lymphocyte ratio (PLR) were significantly changed by palliative radiotherapy on metastatic lymph nodes. The patient achieved persistent response to the re-challenge of immune checkpoint inhibitor, which resulted in survival time reaching 52 months, and is still in extension. Conclusions We supposed that the palliative radiotherapy may lead to the correction of NLR, LMR, and PLR and finally contribute to the efficacy of the re-challenge treatment by PD-1 inhibitor.